2010
DOI: 10.1358/dnp.2010.23.9.1513493
|View full text |Cite
|
Sign up to set email alerts
|

Neu2000, an NR2B-selective, moderate NMDA receptor antagonist and potent spin trapping molecule for stroke

Abstract: Excess activation of ionotropic glutamate receptors, primarily N-methyl-D-aspartate (NMDA) receptors and free radicals, evoke nerve cell death following hypoxic-ischemic brain injury in various animal models. However, clinical trials in stroke patients using NMDA receptor antagonists have failed to show efficacy primarily due to the limited therapeutic time window for neuroprotection and a narrow therapeutic index. In comparison, antioxidants prolonged the time window for neuroprotection in animal models of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…Most investigators agree that the pathologic activation of subtype NMDARs contributes to neuronal death after acute excitotoxic trauma, such as brain ischemia (Arundine and Tymianski, 2004; Guo et al, 2011) and acts as a major mediator. NMDARs consist of a GluN2A subunit that promotes neuron protection, whereas GluN2B-containing NMDARs mediate excitotoxicity (Cho et al, 2010). In the present study, the data showed that Pra-C reverses the upregulation of GluN2B induced by NMDA, implying that the neuroprotection of Pra-C is likely to antagonize a particular NMDAR subunit.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Most investigators agree that the pathologic activation of subtype NMDARs contributes to neuronal death after acute excitotoxic trauma, such as brain ischemia (Arundine and Tymianski, 2004; Guo et al, 2011) and acts as a major mediator. NMDARs consist of a GluN2A subunit that promotes neuron protection, whereas GluN2B-containing NMDARs mediate excitotoxicity (Cho et al, 2010). In the present study, the data showed that Pra-C reverses the upregulation of GluN2B induced by NMDA, implying that the neuroprotection of Pra-C is likely to antagonize a particular NMDAR subunit.…”
Section: Discussionsupporting
confidence: 53%
“…Overactivated NMDA receptors are permeable to Na + , K + , and Ca 2+ ions, among which excess Ca 2+ ions is linearly correlated with neuronal cell death triggered by intracellular Ca 2+ -dependent cascades. Many researchers have focused on the extensive studies of GluN2B antagonists because of the ability to potentially cure various CNS diseases (Brown et al, 2011;Cho et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Most investigators agree that pathologic activation of subtype NMDAR contributes to neuronal death after acute excitotoxic trauma, such as brain ischemia and acts as the major mediator . NMDAR consists of GluN2A subunit that promotes neuron protection, whereas GluN2B‐containing NMDAR mediates excitotoxicity . In the present study, the data showed that FLL reverses the upregulation of GluN2B induced by NMDA, implicating the neuroprotection of FLL is likely to antagonize a particular NMDAR subunit.…”
Section: Discussionsupporting
confidence: 55%
“…In the area of NMDA receptors, development of allosteric modulators, other than the NTD-binding GluN2B-selective agents, has been lagging. Individual compounds such as felbamate (Figure 4) (Chang and Kuo, 2008; Kleckner et al, 1999) and neu2000 (Figure 4) (Cho et al, 2010) appear to also represent NAMs and further work is necessary to better define their sites of action. In the past year, however, three new classes of drugs have emerged that can negatively modulate NMDA receptor function.…”
Section: 0 Recently Identified Negative Allosteric Modulators Of Nmmentioning
confidence: 99%